U-shaped association between myeloperoxidase levels and anxiety risk: a cross-sectional study in a Chinese population - Zhou, Junteng; Kong, Qihang; Liu, Xiaojing; Huang, Yan (Frontiers in public health, 2025)
This study investigates the association between myeloperoxidase (MPO) levels and anxiety risk in Chinese adults and explores potential effect modifiers, with implications for neuroinflammatory biomarker-guided anxiety prevention strategies. Using cross-sectional data from 30,418 adults undergoing routine health examinations (July 2020-June 2021), anxiety severity was assessed via the Self-Rating Anxiety Scale (SAS; score ≥ 50 as clinically relevant). Plasma MPO was quantified by ELISA. Multivariate logistic regression, restricted cubic splines (RCS), threshold effect analysis, and subgroup interactions were conducted to evaluate nonlinear associations. A U-shaped relationship between MPO and anxiety risk was identified. In fully adjusted models, participants in the lowest (Q1: ≤29.77 ng/mL, OR = 1.15, 95% CI: 1.03-1.28, = 0.01) and highest quintiles (Q5: ≥47.3 ng/mL, OR = 1.17, 95% CI: 1.05-1.31, = 0.004) exhibited significantly elevated anxiety risks compared to the reference quintile (Q2: 29.8-34.7 ng/mL). RCS analysis confirmed a nonlinear association ( for nonlinearity < 0.01), with an inflection point at 30 ng/mL: below this threshold, each 1 ng/mL MPO increase reduced anxiety risk (OR = 0.982, CI: 0.970-0.994), while levels above it heightened risk (OR = 1.004, CI: 1.001-1.008). Diabetes mellitus significantly modified this relationship ( -interaction = 0.028), with diabetic individuals showing amplified risks at higher plasma MPO (Q5 OR = 1.84 vs. non-diabetic Q5 OR = 1.15). Plasma MPO demonstrates a U-shaped association with anxiety risk independent of cardiometabolic confounders. Diabetic individuals exhibit heightened susceptibility to MPO-related anxiety, suggesting synergistic neuroinflammatory pathways. Monitoring MPO may aid in risk stratification and personalized interventions, particularly in populations with diabetes.